Nore1a drives Ras to flick the P53 senescence switch - Donninger, Howard (Mol Cell Oncol, 2015)
RAS-induced senescence is a protective mechanism to avoid unrestricted cell growth due to aberrant mitogenic signals; however, the exact mechanism by which RAS induces senescence is not known. We recently identified a novel pathway linking RAS to p53 via NORE1A and HIPK2 that mechanistically explains how Ras induces senescence.